Pentingnya Kemampuan Menguasai Bahasa Inggris bagi Calon Pustakawan Indonesia dalam Meningkatkan dan Mempertahankan Profesi di Era Digital - Ameliya, Rahma; Namo, Rizqi; Amira, Ummi Afzah; Ramadhina, Widya; Yusniah, Yusniah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study discusses the Importance of Mastering English for Prospective Indonesian Librarians in Improving and Maintaining a Profession in the Digital Era. This study aims to find out that prospective librarians must prioritize the importance of English in their profession in today's digital era. The research method used is the literature study method to find out more deeply about a series of activities related to the method of collecting library data, reading, recording, and managing research materials (Zed, 2008: 3). In general, literature study is a way to solve problems by tracing the sources of writing that have been made before. The data needed in this study can be obtained from library sources or documents, such as from textbooks, journals, scientific articles, as well as review literature containing the concepts to be researched. Research with the study of literature does not have to go down to the field and meet with respondents. The results of this study show that mastering English can increase